On the Kabīsa of the Saffarid Amīr Khalaf ibn Aḥmad - Cristoforetti, Simone (Annali di Ca’ Foscari: Serie Orientale, 2017)
The Persian risāla titled Nawrūznāma is a classical work of adab, featuring an account on the history of Iranian calendar and materials (notices, anecdoctes etc.) about courtly and popular customs linked with the Iranian New Year Day. Here we will discuss an isolated notice about an intervention on the solar calendar of the Iranian tradition performed by Khalaf ibn Aḥmad, amīr of Sīstān. The inaccuracy of the Nawrūznāma on historical and astronomical matters does not reduce the importance of this ancient source as a literary work, revealing of its own time's mindset. In fact, the text gives us a plausible clue about the importance of the long reign of Khusraw I for the history of Persian chronology, thus supporting some of the hypotheses traced out by modern scholars. Moreover, it recounts of actual celebrations of the beginning of Spring – to be called Nawrūz – at the time of Abbasid caliph al-Ma’mūn. The conclusion is that, although roughly, the Nawrūznāma not only corroborates other extant sources on the existence of alternative – or parallel – ways of time-reckoning in the Iranian world, but also opens the way for a more precise reconstruction of the relation between a well-ordered social life and kingly governance, that, in Seljuk times, was going to be increasingly thought as essential.